2019
DOI: 10.1002/cjce.23505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light irradiation on esterification of oleic acid with ethanol catalyzed by immobilized Pseudomonas cepacia lipase

Abstract: The present study demonstrates the effect of light irradiation on the esterification of oleic acid catalyzed by immobilized Pseudomonas cepacia lipase. The reaction rates of all the experiments under light irradiation were found to be higher than dark conditions. The kinetics of reactions supported the Ping‐Pong Bi‐Bi mechanism with dead end inhibition by both the alcohol and acid substrates. Moreover, circular dichroism (CD) spectroscopy was used to analyze the effect of light on lipase enzyme. The CD spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[ 7–10 ] It has been reported that various matrices such as synthetic, organic, and biological polymers can be used as support materials for enzyme immobilization. [ 11–17 ] Materials recommended as support in many instances are not suitable for industrial processing procedures due to their low mechanical strength, unsuitable chemical functionality, and inappropriate physical conditions. [ 18–21 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7–10 ] It has been reported that various matrices such as synthetic, organic, and biological polymers can be used as support materials for enzyme immobilization. [ 11–17 ] Materials recommended as support in many instances are not suitable for industrial processing procedures due to their low mechanical strength, unsuitable chemical functionality, and inappropriate physical conditions. [ 18–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] It has been reported that various matrices such as synthetic, organic, and biological polymers can be used as support materials for enzyme immobilization. [11][12][13][14][15][16][17] Materials recommended as support in many instances are not suitable for industrial processing procedures due to their low mechanical strength, unsuitable chemical functionality, and inappropriate physical conditions. [18][19][20][21] Three-dimensional (3-D) polymeric matrices with nano-, micro-, and macropore structures are desirable in many biomedical applications, including catalysis, drug delivery, and protection of proteins, enzymes, DNA, and other biomacromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most commonly used non-immobilized (free) lipases for esterification or transesterification reactions are those from the microorganisms Rhizomucor miehei [ 36 ], Candida. rugosa [ 37 ], and Pseudomonas cepacian [ 38 ]. Immobilized lipases such as Novozyme 435 ( C. antarctica lipase B, CALB) [ 39 ], Lipozyme RM-IM (lipase from R. miehei ), and Lipozyme TL-IM (lipase from T. lanuginosus ) [ 40 ] are also commercially available.…”
Section: Introductionmentioning
confidence: 99%